1999
DOI: 10.1007/s004020050410
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol is elevated in patients with Achilles tendon ruptures

Abstract: Forty-one patients were analyzed after surgical treatment of Achilles tendon ruptures. The following parameters served as the outcome measure: (1) duration of wearing cast, (2) length of hospital stay, (3) outpatient treatment, (4) time of absence from work, (5) complications, (6) re-rupture rate, (7) subjective evaluation by patients, (8) scar condition, (9) ability to stand on tiptoes, (10) Thompson test, (11) movement of talocrural joint, (12) circumference data of lower extremity, (13) radiographs, (14) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…This finding is not surprising given high serum TC concentrations can contribute to the development of Achilles tendon ruptures [11]. Mathiak et al reported that 83% of patients with Achilles tendon ruptures had elevated serum cholesterol levels; interestingly, only 19% were aware of their disease [8]. Klemp et al reported 38% of patients with juvenile familial hypercholesterolemia had musculoskeletal system manifestations [7].…”
Section: Discussionmentioning
confidence: 87%
“…This finding is not surprising given high serum TC concentrations can contribute to the development of Achilles tendon ruptures [11]. Mathiak et al reported that 83% of patients with Achilles tendon ruptures had elevated serum cholesterol levels; interestingly, only 19% were aware of their disease [8]. Klemp et al reported 38% of patients with juvenile familial hypercholesterolemia had musculoskeletal system manifestations [7].…”
Section: Discussionmentioning
confidence: 87%
“…There is a reported association between tendon health and high cholesterol [45,46], although most of these studies have limitations in methodology. In addition, familial hypercholesterolemia (extremely high and sustained serum lipid levels) is associated with tendon disease/rupture [47 -49], which suggests that systemic lipids negatively affect tendons.…”
Section: Potential Mechanisms For the Associationmentioning
confidence: 96%
“…Study done by Mathiak et al found high cholesterol in 83% of people with Achilles tendon ruptures [11]. Klemp et al showed musculoskeletal manifestation found in 38% of juvenile hypercholesterolemia and showed soft tissue manifestation resolved in 63% of patients after receiving antilipidemics [27].…”
Section: Discussionmentioning
confidence: 99%
“…In substantiating risk factors for cuff pathology, studies were done; there were few studies which showed raised serum cholesterol in patients with Achilles tendon ruptures [11]. This study was performed in the western world and patients with rotator cuff tear were found to be hypercholesterolemic [4].…”
Section: Introductionmentioning
confidence: 91%